Dissociable cost and benefit encoding of future rewards by mesolimbic dopamine. - Gan, J; Walton, M; Phillips, P (2010)
Reward-predicting cues evoke activity in midbrain dopamine neurons that encodes fundamental attributes of economic value, including reward magnitude, delay and uncertainty. We found that dopamine release in rat nucleus accumbens encodes anticipated benefits, but not effort-based response costs unless they are atypically low. This neural separation of costs and benefits indicates that mesolimbic dopamine scales with the value of pending rewards, but does not encode the net utility of the action to obtain them.